2022
DOI: 10.1097/md.0000000000029258
|View full text |Cite
|
Sign up to set email alerts
|

Duplex ultrasound for assessing vascular impairment after supracondylar humerus fractures

Abstract: Background: Supracondylar humerus fractures (SHF) are the second most common fracture in children and the most common fracture in children under seven years. Subtle neurovascular lesions in displaced SHF may be underdiagnosed clinically, but their sequelae can mean life-long symptoms. Here we show that color-coded duplex ultrasound (DUS) could help to identify these patients.Methods: We reviewed records of 229 children who had recovered from SHF. Ninety patients were available for detailed questionnaires, in-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…With ultrasound guidance, Bobby achieved a success rate of 94% in the reduction of a closed forearm fracture, which helped to minimize unnecessary damage during the reduction process [ 24 ]. Storch et al [ 25 ] reported that ultrasound is the preferred method for assessing the integrity of the articular cartilage hinge in children with undisplaced lateral humeral condyle fractures. Li et al [ 26 ] used ultrasound-guided reduction and Kirschner wire fixation for 44 patients with displaced and rotated lateral humeral condyle fractures, achieving satisfactory reduction and elbow function in 42 patients.…”
Section: Discussionmentioning
confidence: 99%
“…With ultrasound guidance, Bobby achieved a success rate of 94% in the reduction of a closed forearm fracture, which helped to minimize unnecessary damage during the reduction process [ 24 ]. Storch et al [ 25 ] reported that ultrasound is the preferred method for assessing the integrity of the articular cartilage hinge in children with undisplaced lateral humeral condyle fractures. Li et al [ 26 ] used ultrasound-guided reduction and Kirschner wire fixation for 44 patients with displaced and rotated lateral humeral condyle fractures, achieving satisfactory reduction and elbow function in 42 patients.…”
Section: Discussionmentioning
confidence: 99%